Pilomatrixoma presenting as nontuberculous mycobacterial infection. - Vergadi, E.; Lagoudaki, E.; Galanakis, E. (European Journal of Pediatric Dermatology, 2022)
Calcifying epithelioma of Malherbe or pilomatrixoma is a slow-growing benign skin tumor and its diagnosis is usually clinical. However, in the case of secondary superinfection, pilomatrixoma may not be correctly diagnosed with clinical examination. We present the case of a boy with a history of a slow-growing abscess following trauma in a swimming pool that was unresponsive to empirical antibiotics. A provisional diagnosis of non-tuberculous mycobacterial infection was made. Despite empirical treatment, a partial response was observed. Surgical excision and biopsy revealed the presence of a secondarily infected pilomatrixoma. The latter may not be recognized in cases of secondary superinfection and should be included in the differential diagnosis of slow growing skin abscesses that are unresponsive to antibiotics.